An Interdisciplinary Application Based on Constructivist Approach: Teaching of Energy Topics - Güliz AYDIN; Ali Günay BALIM (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this study, the effects of constructivist approach and traditional approach on students’ understanding of “The Work, Power, Energy and Simple Machines” topics were studied. It was studied whether there was a statistically significant difference in cognitive and affective level between the experimental group to whom constructivist approach was applied, and the control group to whom traditional approach was applied in the learning of energy topics with interdisciplinary quality. The research was based on pre-test – posttest quasi-experimental design with control group. Participants were 68 7th grade students. The research was done on the second term of 2004-2005 education year. Before and after the study, the students were given science attitude scale and “The Work, Power, Energy and Simple Machines” achievement test. According to the pre-tests, there wasn’t a statistically significant difference between the science achievement and attitudes of the students, but after the study it was determined that there were statistically significant differences on the cognitive and affective levels in favor of the experiment group